Невідома ревізія Переяславського полку як джерело до історії неурядової старшини. (Zaporizhzhia Historical Review, 2021)
Inspection of Pereyaslav regiment from 1750 is characterized. Individual, service and economic sample data of “neuradova starshyna” of regiment are given in the article. Key words: inspection, regiment, “sotna”, cossack, “neuradova starshyna”, “bunchukovyi” comrade, “viyskovyi” comrade, “znachkovyi” comrade.